2010
DOI: 10.1074/jbc.a109.060954
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of multiple similar ligand-binding repeats in filamin.

Abstract: Because of clerical errors in preparing the figures, in Fig. 1A, the last portions of the mouse and human TILRR sequences are not aligned with the consensus sequence, and the human form is mislabeled as 716 amino acids (aa). In Fig. 2C (and on page 7227, right column, line 4), the most potent form of the human protein is mislabeled as 710 aa. Supplemental Fig. S1 correctly shows the alignment and the length of the human TILRR protein as 715 aa, with the most potent form, lacking the N-terminal 6 aa, as 709 aa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…S4 A and B). Even though the binding kinetics of those ligands have not been measured before, the equilibrium binding constants (K D ) of the three peptides calculated from the kinetics agree well with bulk measurements (Table S3) (25). It is interesting to note that with K D values in the micromolar range and above, as well as lifetimes below a second, all those interactions are very dynamic.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…S4 A and B). Even though the binding kinetics of those ligands have not been measured before, the equilibrium binding constants (K D ) of the three peptides calculated from the kinetics agree well with bulk measurements (Table S3) (25). It is interesting to note that with K D values in the micromolar range and above, as well as lifetimes below a second, all those interactions are very dynamic.…”
Section: Resultssupporting
confidence: 61%
“…The subsequent build-up of mechanical tension can then relieve the autoinhibition of the other domains promoting strong anchoring. The necessity of multiple parallel bonds for stable anchoring is in accord with the idea that the multiple binding sites of filamin can also induce clustering of transmembrane receptors (10,25). Alternatively, filamin interactions may be substituted or stabilized by other adaptor molecules.…”
Section: Discussionsupporting
confidence: 54%
“…Sequence and structural analysis has revealed that FLN repeats exist as domain pairs e.g. 16/17, 18/19 and 20/21 (Lad et al 2007;Heikkinen et al 2009) with multiple β-integrin interaction sites functionally identified (Ithychanda et al 2009). …”
Section: Filamin Domain Organisation and Structurementioning
confidence: 99%
“…The issue of whether FLNs can heterodimerise is not fully resolved; FLNB/C repeat 24 heterodimers were observed by in vitro cross-linking assays, but the combinations of FLNA/B or FLNA/C were not (Himmel et al Fig. 1 Schematic representation of filamin cross-linking F-actin and clustering integrin receptors at the plasma membrane (Ithychanda et al 2009) (Sheen et al 2002).…”
Section: Filamin Domain Organisation and Structurementioning
confidence: 99%
See 1 more Smart Citation